Clinical Characteristics of Cryoglobulinemia With Cardiac Involvement in a Single Center - He, Kun; Zhang, Yun; Wang, Wei; Wang, Yu; Sha, Yue; Zeng, Xuejun (Frontiers in Cardiovascular Medicine, 2022)
Background: Cryoglobulinemia is a syndrome characterized by the presence of cryoglobulins (CGs) in serum, and cardiac involvement is a rare occurrence that can affect treatment and prognosis. This study aimed to explore the clinical characteristics of cryoglobulinemia with cardiac involvement. Methods: 108 patients diagnosed with cryoglobulinemia who were admitted and treated in Peking Union Medical College Hospital(PUMCH) between June 1985 and June 2019 were enrolled in the present study. Clinical characteristics, therapy, and prognosis of patients with cardiac involvement were retrospectively analyzed. Results: The cryoglobulinemia with cardiac involvement was found in 7 patients, thus reaching the incidence of 6.5%. Heart failure was the main cardiac manifestation found in these patients, all with the involvement of external cardiac organs. Laboratory examinations showed significant elevation of N-terminal brain natriuretic peptide precursor (NT-proBNP) and brain natriuretic peptide (BNP) with negative troponin (cTnI). Electrocardiogram (ECG) was generally normal or only showed low-flat and biphasic multi-lead T waves. Echocardiography was performed in 6 patients, all of whom showed enlargement of heart cavity. Five patients had reduced left ventricular myocardial contractible motion with decreased ejection fraction, 3 patients had pericardial effusion, and 1 patient had left ventricular hypertrophy or severe aortic insufficiency. Cardiac magnetic resonance imaging showed delayed myocardial enhancement in 2 patients. One patient underwent a myocardial biopsy, which showed perivasculitis. Condition in 6 patients who received active treatment targeting improved in the early stage. Three patients（3/7, 42.9%）died due to disease progression during follow-up period. Conclusions: Cryoglobulinemia with cardiac involvement is a rare but serious condition that has relatively high risk of death. When patients with cryoglobulinemia without underlying heart disease experience heart failure, chest pain, or elevation of asymptomatic NT-proBNP and BNP, there is a high possibility of cardiac involvement, even if the electrocardiogram and troponin are negative. Further examinations such as echocardiography, cardiac magnetic resonance imaging, and myocardial biopsy examination could contribute to the diagnosis. Cardiac manifestations could be timely reversed after active targeted treatment. NT-proBNP and echocardiography could be used for the monitoring of disease efficacy.